China’s President’s Power And His Response To Covid-19 Outbreak - Roziqin, Roziqin (LPPM Universitas Lampung, 2021)
Right now, all countries are facing the Covid-19 outbreaks. Some analysts, including President Trump, blame the People's Republic of China (PRC, known as China) for the outbreak. The pandemic makes most of the countries fell into recession. Only China emerged from the other economies that went into recession with a positive growth rate in 2020. With 1.4 billion people, China's ability to manage Covid-19 risk is impressive. China works together with many countries, including World Health Organization (WHO), facing the pandemic. It made the genome sequence available for release and shared treatment with other countries and many parties. Since the end of May 2020, China has been offering its Covid vaccines to the rest of the world. This action is a continuation of the mask donation so that China can reverse the image, which was initially accused of being the source of the problem, now to become a helper god. The handling of the Covid-19 pandemic cannot be separated from Xi Jinping's role as President of the PRC. His role will be related to the Chinese political system. Therefore, this research will study the Chinese political system, China President's power, and the power used to handle the Covid-19 outbreaks. My study showed that the centralized government, the President's strong position, supported with good governance capital help the country successfully handle the pandemic.